Kajian Pengaruh Sosial Ekonomi Terhadap Investasi Dalam Negeri (Studi Kasus pada 34 Provinsi di Indonesia Tahun 2019-2021) - Ikhlasul Fajri; Fedi, Siti Zuliana (Universitas Islam Negeri Alauddin Makassar, 2024)
Improving people's welfare after Covid-19 and the threat of a global recession in 2023 is one of the current economic development priorities. Investment is believed to be one way out to improve people's welfare. Social and economic factors are believed to play an important role in increasing investor interest in investing. Therefore, it is necessary to analyze the social and economic factors that influence interest in investing in Indonesia. Analysis will be carried out using statistical tests to provide empirical evidence. The analytical method used in this research is panel data regression with the dependent variable being domestic investment. The best model obtained from the results of the analysis is the random effect model (REM). The results of the analysis show that the variable percentage of the workforce and the Covid-19 pandemic have no significant effect on investment interest. The crime rate has a negative and significant effect on investment interest and there are two variables that have a positive and significant effect on investment interest, namely the ratio of road length to area and HDI